CONVERTING TO ISLAM - Segu Atio (Al-Albab, 2012)
Despite the fact that early Chinese expeditions to this country were led by a Muslim Chinese named Zheng He (Cheng Ho), the overwhelming majority of Chinese Indonesians currently embrace religions other than Islam. This article aims to give a first-hand account of a Chinese woman who converted to Islam and the stereotypical opinion commonly held among Chinese Indonesians, particularly those living in Pontianak, about it. This article also looks at why a conversion to Islam is always seen with a puzzled frown. Keyword: Convert, Islam, Chinesse